Ethanol production from halophyte Juncus maritimus using freezing and thawing biomass pretreatment. (January 2016) - Smichi, Neila; Messaoudi, Yosra; Moujahed, Nizar; Gargouri, Mohamed
Abstract: Juncus maritimus contains (41.5 ± 0.3)% cellulose and (31.34 ± 0.2)% hemicellulose on dry solid (DS) basis and has the potential to serve as a low cost feedstock for ethanol production. Dilute acid or freezing/thawing pretreatments and enzymatic sacchariﬁcation were evaluated for conversion of halophyte plant from J. maritimus cellulose and hemicelluloses to monomeric sugars. The maximum concentration of released glucose from J. maritimus (53.78 ± 3.24) g L −1 ) by Freezing/thawing pretreatment and enzymatic sacchariﬁcation (55 °C, pH 5.0 and 48 h) using CellicCTec2 from Novozymes and (49.14 ± 5.24) g L −1 obtained by dilute acid pretreatment. The maximum yield of ethanol from acid pretreated enzyme sacchariﬁed J. maritimus hydrolyzate by Saccharomyces cerevisiae strain was (84.28 ± 5.11)% of the theoretical yield with a productivity of (0.88 ± 0.16)g L −1 h −1 . It was (90.87 ± 1.94)% of the theoretical yield with a productivity of (1.04 ± 0.10) g L −1 h −1 for freezing/thawing pretreated plant and enzymatic hydrolysis by CellicCTec2. Highlights: Conversion of halophyte plant, Juncus maritimus, into bioethanol. Two different methods of pretreatment were tested. The maximum ethanol yield was 90.87% of the theoretical yield of yeast.